2018
DOI: 10.1002/da.22762
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for anxiety: A systematic review and meta-analysis of randomized controlled trials

Abstract: Yoga has become a popular approach to improve emotional health. The aim of this review was to systematically assess and meta-analyze the effectiveness and safety of yoga for anxiety. Medline/PubMed, Scopus, the Cochrane Library, PsycINFO, and IndMED were searched through October 2016 for randomized controlled trials (RCTs) of yoga for individuals with anxiety disorders or elevated levels of anxiety. The primary outcomes were anxiety and remission rates, and secondary outcomes were depression, quality of life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
117
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 62 publications
4
117
1
6
Order By: Relevance
“…Our results contrast with previous findings of yoga’s effectiveness in reducing symptoms in mood and anxiety disorders [ 51 59 ]. A previous meta-analysis on yoga for depression found medium-large effect sizes for yoga compared to usual care (standardized mean difference (SMD) of -0.69), for yoga compared to relaxation (SMD of -0.62), and for yoga compared to exercise (SMD of -0.59) [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results contrast with previous findings of yoga’s effectiveness in reducing symptoms in mood and anxiety disorders [ 51 59 ]. A previous meta-analysis on yoga for depression found medium-large effect sizes for yoga compared to usual care (standardized mean difference (SMD) of -0.69), for yoga compared to relaxation (SMD of -0.62), and for yoga compared to exercise (SMD of -0.59) [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The effects of yoga on mood and anxiety disorders have been reviewed by several authors [ 51 59 ]. These systematic reviews and two meta-analyses concluded that there is some evidence of yoga being effective for mood and anxiety disorders, but all mention serious methodological drawbacks of the included randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…This was associated with frequency of yoga practice rather than overall length of practising. Importantly, our survey found that participants perceived yoga as helpful in managing a wide range of health conditions, most notably musculoskeletal conditions and mental health, consistent with findings in the USA2 and clinical trials 11 13. This suggests that yoga is used in the UK to manage health conditions and support well-being and has further potential to support self-care of debilitating and costly health disorders.…”
Section: Discussionsupporting
confidence: 79%
“…There is growing evidence that yoga is an effective multi-component health intervention that reduces stress, increases physical activity and improves well-being 5–7. Clinical studies provide preliminary support for the effectiveness of yoga as an adjunct treatment for a range of chronic conditions such as depression,8 9 anxiety,10 11 lower back pain12 13 and type 2 diabetes 14 15. Potential physiological mechanisms include down-regulation of the hypothalamic–pituitary–adrenal (HPA) axis and sympathetic nervous system and reduced inflammatory markers 6 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…It became not only popular due to its positive physical and psychological effects in the healthy [2][3][4]. It also showed preventive and therapeutic effects in patients with various common diseases, including cardiovascular diseases [5][6][7], especially high blood pressure [8,9], neuro-psychiatric disorders [10,11] such as ADHD [12,13], post-traumatic stress disorder [14,15], anxiety disorders [16][17][18], depression [19][20][21] and schizophrenia [22,23]. In particular, the significant reduction in stress [24][25][26], and the positive effects on diseases that often occur in old age, such as Alzheimer's [27] and Parkinson's [28], and where conventional medicine is still limited in cure, makes Yoga an exciting current therapeutic modality.…”
Section: Introductionmentioning
confidence: 99%